Intermediate College Writing Building and Practicing Mindful Writing Skills - Atkinson, Dawn; Corbitt, Stacey (Open textbook library., 2022)
Welcome to Intermediate College Writing: Building and Practicing Mindful Writing Skills, an open textbook designed for use in university‐level courses that focus on cultivating study skills alongside effective academic and workplace writing skills. It offers a no‐cost alternative to commercial products, combining practical guidance with interactive exercises and thoughtfully designed writing opportunities. This textbook’s modular design and ample coverage of topics and genres means that it can be used flexibly over semester‐long or stretch courses, allowing instructors and students to select the chapters that are most relevant for their needs. By blending new material with reviews of key topics, such as academic integrity, the chapters provide fresh perspectives on matters vital to the development of strong writing skills. The book adapts, builds upon, and expands material covered in our first open textbook, Mindful Technical Writing: An Introduction to the Fundamentals (Atkinson & Corbitt, 2021).